Generalized Structural Design Scheme for Bogie Frame Assembly Welding Fixtures in Urban Rail Transit Vehicles - WANG Dalu (Chengshi guidao jiaotong yanjiu)
［Objective］ Conventional assembly welding fixtures for vehicle bogie frames in urban rail transit do not meet the requirements for reducing production costs, simplifying operational difficulty, improving the utilization rate of process equipment, and saving space. It is necessary to adopt more reasonable mechanical design concepts to optimize fixture structures and develop a generalized structural design scheme. ［Method］ Four main structural types of existing bogie frames for urban rail transit vehicles are listed, and the general design principles for fixtures associated with these structures are summarized. Based on determining the selection of reference positioning planes and thrust positioning reference planes, and clarifying the clamping method of the fixtures, the generalized structural design scheme (including positioning structure and clamping structure) is optimized. The allowable stress of the screw pair in the sliding screw drive, the self-locking performance of the thread, the strength of the nut and screw, and the thread strength are verified, resulting in an optimized generalized fixture design scheme. ［Result & Conclusion］ The optimized scheme adopts a self-positioning design structure that allows for single-person operation, ensuring even distribution of deformation dimensions in welded components and reducing unequal welding tolerances caused by welding deformation.